Talent Commodification In Ruangguru Marketing Interests: Analysis of The Show Program Clash of Champion - Fuandani Istiati; Halla Sayyidah Muflichah (POPULIKA, 2025)
Program Clash of Champions by Ruangguru is an essential example of content commodification in Indonesia's educational entertainment sector. Program Clash of Champions broadcast on the YouTube platform as a gameshow, designed as an academic and competitive show for students by combining educational and entertainment content. This show has proven effective in attracting the audience's interest in watching it and serving as a promotional event brand for the Teacher's room. This research examines and analyzes how commodification practices occur in this program by referring to political economy theory. The first commodification practice is optimizing the use of social media, such as the YouTube platform. Second is the gamification element, where not only talent is involved in the game but also the audience so that the audience can feel the effects of dramatization and interactivity. This research uses an interesting case study method, a qualitative descriptive approach. The research results show that the program broadcasts Clash of Champions. It's not purely an educational show but also a marketing tool from Ruangguru. Keywords: Commodification; Social Media; YouTube Content.